Omni-Channel Marketing Strategy for Lake Toba Indonesia Tourist Destinations in Attracting Foreign Tourists - Situmorang, Milton; Widodo, Slamet (Sinergi International Journal of Economics, 2024)
Lake Toba in North Sumatra, Indonesia, is a region of significant potential for attracting international tourists due to its exceptional natural beauty and cultural richness. However, the current influx of foreign visitors remains low compared to other leading tourist destinations in Indonesia. This research investigates the development and implementation of an omni-channel marketing strategy aimed at enhancing Lake Toba's appeal to international travelers. The study employs a mixed-methods approach, combining qualitative interviews with key stakeholders in the tourism industry and quantitative analysis of tourist behavior data. Key challenges identified include inadequate infrastructure, insufficient promotional efforts, and intense global competition. The research proposes strategies that integrate digital and physical marketing channels, personalize content to meet diverse traveler preferences, and leverage advanced technologies such as artificial intelligence (AI) and virtual reality (VR). The findings suggest that an omni-channel approach can create a more cohesive and engaging tourist experience, thereby increasing Lake Toba's competitiveness in the global market. The research also highlights the broader implications for digital transformation in Indonesia's tourism sector and suggests directions for future studies focused on long-term impacts and scalability of omni-channel strategies.